Examining job satisfaction among analysts: the impact of departmental integration, role clarity, and it responsibilities. (June 2019) - Green, Emilee; Rossler, Michael T.
Previous research has indicated that a lack of departmental integration and role clarity, as well as departmental expectations to provide information technology support beyond a crime-mapping capacity, are some of the most common occupational issues for crime and intelligence analysts. Although these challenges are noted, little research has attempted to test the hypotheses that these occupational issues are empirically related to analysts' satisfaction with their jobs. Drawing upon a survey of 113 members of the International Association of Crime Analysts, the current inquiry tests whether departmental integration, role clarity, and information technology responsibilities impact analysts' job satisfaction. Findings indicate that when analysts have a greater perception that their work is fully integrated into the mission of the department, and their role is clear, that job satisfaction is higher. Implications for future research and policy are also discussed.